Bürgergeld und die Zukunft des Sozialstaats; Citizen's income and the future of the welfare state - Michael Opielka; Wolfgang Strengmann-Kuhn (Wirtschaftsdienst, 2022)
– The authors discuss the reform of basic security in the direction of a "citizen's income" in the coalition agreement of the new "traffic light coalition" at the federal level against the background of fundamental considerations on the future of the welfare state, including those from the "Schleswig-Holstein Future Laboratory". They see the reform of the citizen's income as an incrementalist step toward a basic income and discuss their thesis on four topics: a) the question of the level of the basic income, b) the problem of counting other incomes, c) the relationship to the basic pension and citizen's insurance, and d) the basic income for children.
Keywords: J65; J68; 330; Grundeinkommen; Sozialstaat; Deutschland